Mortality due to accidents in children under 15 years of age. Villa Clara, Cuba: 2015-2019 - González-Rodríguez, Irén de la Caridad (2023)
Accidents are frequent events in the pediatric age and constitute a complex event in which multiple factors may intervene, which are related to the particular characteristics of each society. To characterize accident mortality in children under 15 years of age. Cross-sectional descriptive observational research was carried out, characterizing mortality due to accidents in children under 15 years of age in Villa Clara in the period from January 2015 to December 2019. The information was obtained from the national and provincial registry of deaths. Twenty-two accidents were counted, with a rate of 3.76 per 100 000 inhabitants; the most affected age group was 5 to 9 years old, with 9 deaths, and a rate of 2.32 per 10 000 inhabitants, male sex, with 3.20 deaths per 10 000 male children of those ages. In these five years, the municipalities that have suffered more than others the occurrence of fatal accidents in their children, were Cifuentes, Quemado de Güines and Manicaragua, where they were the months with the highest accident rate, from July to October. Among the types of accidents, those with the highest incidence were drowning, followed by burns, and among the types of injuries, drowning and cranial trauma.